Relativity of Peers: Learning Efficiency of Secondary Students - Al M. Lolos; Annerill P. Lorio; Caryll L. Martinez; Hassanal P. Abusama; Khalid Yasper M. Tangkli; Mary Nelle Jireh S. Falsario; Zaira Aleiah Kim F. Consebit (Universitas Pendidikan Indonesia (UPI), 2021)
This study aimed to know how peers can take over a secondary student’s learning efficiency and if this relation is that cohesive. To gather data for the study, interviews, with the use of guide questionnaires, were conducted with the participants selected through purposive sampling. Data collected were analyzed through thematic analysis. The participants were five (5) secondary students of Sultan Kudarat State University – Laboratory Science High School. This study shows that the following points were made: (1) There are a lot of ways peers can assert changes to a student’s academic performance. These can be manifested through all the statements that the participants gave to the researchers; (2) A larger number of peers can easily get a student persuaded in doing activities unrelated to their academics; (3) The length of friendship between the peers and the student matters by means of the cohesiveness of peers on the learning efficiency of a student; (4) The affiliation of peers toward the learning efficiency of students is very enormous that it plays a vital role in the things that could happen to a student’s learning at school and everywhere; (5) There are tendencies that peers can’t affect a student’s learning efficiency. These conclusions can be of help to students, parents, teachers and future researchers.